(untitled) (Biological Sciences - PJSIR, 2005)
A study has been carried out to determine the effect of humidity on the disintegrant property of a-cellulose in tablet formulations. Paracetamol tablets containing a-cellulose (5% w/w) as disintegrant were employed in the study. The tablets were tested for hardness, disintegration time and dissolution rates before and after their exposure to different relative humidities (RH) of 1%, 78% and 100% at 30 °C (room temperature) for various time intervals upto a maximum of 2 weeks. Humidity effect on the particle structure of a-cellulose was determined by photomicroscopy. Tablets exposed to RH of 1% and 78% disintegrated very fast, within a minute, similar to the fresh samples. In contrast, tablets exposed to RH 100% for ³ 24 h failed to disintegrate within 60 min even though the tablets became softer. Tablet dissolution rate was also markedly impaired in this set of tablets. Exposure of the a-cellulose powder to RH 100% for 24 h caused the particles to gel, which accounted for the impairment of its disintegrant property.